Effect of thickness and CAD‐CAM material on fatigue resistance of endodontically treated molars restored with occlusal veneers. Issue 2 (2nd October 2022) - Noronha, Mayara dos Santos; Carvalho, Marco Aurélio de; Do, Anh Quynh; Neto, Vitaliano Gomes de Araújo; Campos, Camila Heitor; Giannini, Marcelo; Magne, Pascal
Abstract: Purpose: To evaluate the influence of the thickness and type of computer‐aided design and computer‐aided manufacturing (CAD‐CAM) material on the fatigue resistance and failure mode of endodontically treated teeth (ETT) restored with occlusal veneers (OV). Materials and methods: Seventy‐five (N = 75) ETT were restored with Herculite XRV in the endodontic access. Five experimental groups (n = 15) were tested. Four groups had two different thicknesses (0.6‐0.7 mm or 1.4‐1.6 mm) and two different CAD‐CAM materials: zirconia‐reinforced lithium‐silicate (LS/Celtra Duo) and composite resin (RC/Cerasmart). The fifth group (control) did not have occlusal veneers. All the specimens were subjected to accelerated fatigue (5 Hz frequency) with an occlusal load increasing up to 1800 N and 131, 000 cycles. The number of cycles was recorded when the machine stopped or at the completion of the test. Fatigue resistance was analyzed using the Kaplan‐Meier survival test (95% significance level, log‐rank post hoc pairwise comparisons). The samples were categorized according to failure mode. The CAD‐CAM materials were examined through scanning electron microscopy (SEM) and energy dispersive X‐ray spectroscopy (EDS). Results: No differences were found between the thicknesses, regardless of the type of the CAD‐CAM material. The thick LS OV outperformed the RC and control groups. The thin RC OV and control groups showed a higher percentage of repairable and possibly repairable failures than the other groups. LS was more homogeneous under SEM, and the EDS analysis detected Si and Zr, but not Li. Conclusions: A larger thickness did not improve the resistance of the CAD‐CAM materials. Thick LS showed a higher cumulative survival rate to fatigue than the RC and control groups. The direct composite alone (control) survived similarly to the experimental groups, except for the thick LS.